Modulation of Various Phytoconstituents in Tomato Seedling Growth and Meloidogyne incognita–Induced Stress Alleviation By Vermicompost Application - Tikoria, Raman; Kaur, Arvinder; Ohri, Puja (Frontiers in Environmental Science, 2022)
In addition to chemical pesticides and fertilizers, the use of vermicompost can help in the management of root knot nematodes (RKN) while also augmented plant growth. The present study is carried out to determine the role of neem-based vermicompost on plant growth during stress produced by Meloidogyne incognita. Vermicompost (Vcom) and soil were mixed in various proportions (0, 20, 40, 60, 80 and 100%) and used to treat tomato plants against nematode infestation. After ten days of inoculation of second stage juveniles of M. incognita, several morphological parameters such as root length, shoot length, root weight, shoot weight, number of galls and number of leaves were evaluated to investigate the plant growth. Various photosynthetic pigments (chlorophyll a, b, total chlorophyll and carotenoid content) and gaseous exchange parameters (photosynthesis rate, intercellular carbondiaoxide intensity, stomatal conductance and transpiration rate) were also investigated in order to better understand plant respiration and response to nematode stress. In biochemical studies, the protein content and unit activity of antioxidative enzymes such catalase, superoxide dismutase, guaiacol peroxidase, glutathione-s-transferase, ascorbate peroxidase and polyphenol oxidase was investigated. Analysis of malondialdehyde (MDA) and hydrogen peroxide (H2O2) contents were also performed to examine the stress caused by nematodes and the effect of vermicompost in overcoming that stress. Aside from that, the influence of vermicompost on several bioactive components of plants was investigated by quantifying non-antioxidative enzymes (ascorbic acid, glutathione and tocopherol levels) and secondary metabolites (total phenolic, total flavonoid and anthocyanin contents). The results of the foregoing experiments reveal a significant increase in all morphological, biochemical, and photosynthetic parameters except MDA and H2O2, which tend to decrease with increasing vermicompost concentration as compared to untreated and nematode infected plants. The current study revealed that vermicompost has a high potential for lowering the nematode stress and enhancing plant growth and development through the augmentation of different bioactive components in plants.